EARLY DIAGNOSIS OF IMMUNE DISTURBANCES AND ITS CORRECTION IN THE TREATMENT OF MULTIORGAN FAILURE AND SEPTIC COMPLICATIONS AFTER OPERATIONS WITH ARTIFICIAL AND ASSIST CIRCULATION - V. S. Suskova; V. I. Emez; L. P. Ermakova; М. N. Kozlova; S. I. Suskova; V. N. Poptsov; D. V. Shumakov; M. L. Semenovsky; E. N. Kazakov (Вестник трансплантологии и искусственных органов)
The study has shown that early diagnosis of the type and degree of immune disturbances in preparation for the operation and the first signs of multiorgan failure and septic complications in the postoperative period in cardiac surgery patients were the rationale for the earlier substitution immunocorrection by immunomodulators of cytokine nature and intravenous immunoglobulin. It allowed increasing the efficiency of the treatment of postoperative complications and lower mortality after operations with artificial and assist circulation.